Discriminação salarial por cor e gênero revisitada: uma abordagem de decomposição contrafactual utilizando regressões quantílicas - Bartalotti, Otavio Augusto Camargo (2007)
The wage inequality, specially the one resulting from discrimination against blacks and women in the labor market, is an important component of the high income concentration of the Brazilian economy. Instead of the majority of studies developed in this area, this work doesn’t adopt the hypoyhesis that the effects of atributes determining wages are constants and identical across the wage distribution. Wage structures for each percentile of income distribution are estimated to white men, black men, white women and black women using Koenker and Bassett (1978) and Machado and Mata (2004)’s quantile regression counterfactual decomposition technique. This provides a more detailed comprehension of the factors that determine wages to different levels of income and a more complete measure of the discrimination against black and women across wage distribution. The discrimination is positively related to the wage distribution quantile to the three groups, pointing out the women and black difficulty to reach better paid jobs. The black women are the most affected by discrimination, followed by white women and black men. To black men the discrimination is lower among the poor and increases in upper levels of income. White women are discriminated across all the distribution, with greater effects among the richest 15%. The black women wages are reduced by gender and color discrimination summed up, therefore they are in the worst situation among the three groups. The education’s return increases to higher quantiles to all groups, increasing the intra-group wage inequality. In addition to this, there is an undervaluation of black’s education in the wage determination and women perceives discrimination on education’s payment only on higher wage levels. The increase in wages obtained with the equalization of education and level of formal work between the discriminated groups and white men indicate that, concerning education, black men and women would have income gains across all the distribution, especially in the higher deciles. To formal work, the population on the lower quantiles would receive the greatest increases in wages.